Polytobacco use and risk perceptions among young adults: The potential role of habituation to risk - Leavens, Eleanor L.S. (Addict Behav, 2018)
INTRODUCTION: Polytobacco use and experimentation is common among young adults. Additional research is needed to determine how these patterns of use impact perceptions of tobacco-related harm and risk. The current study examined whether a relationship exists between an increased number of tobacco products used and decreases in perceptions of harmfulness and health risk. METHOD: Participants (N = 792) completed a survey assessing current/lifetime tobacco use, perceived absolute harmfulness of tobacco/nicotine products and perceived health risk of smoking. For some analyses, participants were grouped by polytobacco use status. RESULTS: Among participants who ever tried a tobacco product, a greater number of products tried was associated with lower perceptions of harm (all p < .05). For e-cigarettes and hookah, nonusers rated tobacco products as more harmful compared to single product, dual, and poly users (all p < .05). Number of products tried predicted perceived harmfulness above and beyond demographic characteristics and polytobacco use status across all products. Similarly, number of products tried predicted perceived health risk above and beyond demographic characteristics and polytobacco use status for both lung cancer and heart disease risk. DISCUSSION: Trying a greater number of tobacco products is associated with lower perceived harmfulness of tobacco products. Prospective studies are needed to determine if experimentation with more tobacco products leads to reductions in perceived risk of tobacco use and subsequent sustained use of tobacco.